(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The following section looks mostly at two centralarticles. First, I will look at one of the essays that has been mostinfluential and has been cited the most times within film theory, LauraMulvey’s ‘Visual pleasure and narrative cinema’ from 1975 (Humm, 1997: 14).Secondly, I will deal with E. Ann Kaplan’s article ‘Is the gaze male?’ from1983. These articles are examples of how psychoanalysis has helped formfeminist film theory over time. Maggie Humm explains this connection betweenfeminism and psychoanalysis in terms of what the two fields have in common.They both focus on gender in relation to identification, and also look at therelationship between unstable identity and repression. “Second, both share keymethods: analysing texts, whether these are films or the unconscious, in termsof codes and as if texts can represent the ‘unsaid’ in everyday life” (15).This means that by making use of psychoanalysis in film analysis one candeconstruct the underlying mechanisms that place women in extremelystereotypical forms on the screen.